Designing Accounting Software Based On Microsoft Access At Toko Bangunan Jaya Indah - Celina Tan; Muhammad Taufik (Universitas Internasional Batam, 2023)
Toko Bangunan Jaya Indah has been operating for approximately 27 years. However, their accounting bookkeeping activities still apply manual recording, which can cause the business owners to be unable to know the business's financial condition. This community service aims to generate an accounting bookkeeping software system through Microsoft Office Access to provide accurate financial reports. In collecting information, we use the method of observation and interview. In addition, we use evidence of transactions based on business operations as our reference to generate bookkeeping software. The output of this accounting software system included a purchase form, sales form, profit and loss report, and balance sheet. The output would guide SMEs to make a better decision making in monitoring their sales and expenses.